Beta-lactam-azasugar hybrid as a competitive potent galactosidase inhibitor - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M.; Puranik, Vedavati G. (Tetrahedron Letters, 2006)
A beta-lactam-azasugar hybrid (polyhydroxylated carbacephem) has been designed and synthesized as a potent glycosidase inhibitor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: beta-Galactosidase; beta-lactam-azasugar; glycosidase inhibitor; hybrid molecules